KARAKTERISTIK GENETIK PADA FAMILI CERVIDAE (Cervus unicolor, Cervus timorensis, dan Axis kuhlii) BERDASARKAN 12SrRNA mtDNA - Wirdateti Wirdateti; Gono Semiadi; Toshinao Okayama (The East Java Biological Society, 2004)
Genetic analysis from three species of Indonesia Cervidae (sambar deer, Cervus unicolor; rusa deer, Cervus timorensis; and Bawean deer, Axis kuhlii) was conducted to analyze their relationship. Tissues and blood from twelve sambar deer, one rusa deer and three Bawean deer were collected and analyzed for 12SrRNA using Primer forward (L1091) and reverse (H1478). The results indicated the amplication of mtDNA were 389 base nucleotide. There were 22 polimorphic sites, which were dominated by transition and gave 9 haplotypes that were 5 in sambar deer, 1 in rusa deer and 3 in Bawean deer.